Kontribusi Pelayanan Terhadap Kepuasan Nasabah Bank Muamalat - Norhayatun Norhayatun (Jurnal Studi Agama dan Masyarakat, 2018)
This study is conducted to investigate  the service to customers’ satisfaction at Bank Muamalat Branch of Sampit. To measure variables: 1) Convenience, 2) customer relationship with employees, 3) technical compensation of officers, and 4) costs. To measure the quality variable of   place of five aspects; 1) physical form (tangibles), 2) reliability, 3) responsiveness, 4)  assurance , and 5) empathy. The proposed hypothesis is that the service effect on customers’ satisfaction. The research populations were 7000 customers. Sampling technique was done using accidental sampling technique with total sample of 32 customers. Data collection techniques used a questionnaire fulfiling the requirements of validity and reliability. Data analysis teachniqe used  simple linear regression analysis technique fulfilling requirements: normality test, linearity and autocorrelation test. From the research data description, they were the variables belonged to high category 3%, medium category 84%, and low category 13%. Meanwhile,  the satisfaction belonged to high category was  22%, medium category  was 53%, and low category was 25%. The problems were related to service and satisfaction for the medium category. This study revealed that   there was an effect of service to customer satisfaction at Bank Muamalat Branch of Sampit about 14.3%.